Book history’s recent methodological trend: national and intemational outlines - Hakapää, Jyrki (Knygotyra, 2024)
About twenty years ago, Robert Darnton famously wrote about how books know no frontiers. Nevertheless, as the discipline of book history has established itself around the world, many comprehensive works on the research field have determined themselves according to the nation-state borders. As national needs have been recently fulfilled in many countries, international and cosmopolitan themes and studies have received a new kind of support. In a world marked by globalization, such a change in attitude seems reasonable. Those book historians who hear the call must determine their research work anew and find new, interesting frameworks for their studies. What can they find? What possibilities do these new choices offer? The international approaches may offer new insights about the past, but do they also offer better chances to secure project funding and reach contemporary readers? Researchers in smaller countries, where local book culture has been more or less dependent on foreign contacts and influences for a long time, might question if the cosmopolitan attitude has ever truly been forgotten. A new methodological turn towards transnationalism and diversity might seem less relevant when looking for examples from the Baltic Sea region, where languages, cultural and trade networks, social systems, and even states have continuously changed. In the end, contemporary book history researchers do not only have to answer whether they want to follow new methodological suggestions but also what they want to seek when examining history. The presentation discusses three topics related to the recent methodological trend that seeks to move beyond nation-states as the main object or framework of book history studies. First, the juxtaposition between national and international approaches is examined. Additionally, other concepts like "local," "regional," "domestic," "transnational," and "multinational" are conceptualized and compared to each other. Secondly, researchers should seek alternative defining frameworks: studies focusing on linguistic, social, or gender borders, rather than a national approach, would offer further insights. Finally, specific methodologies have been created for international history studies; comparative studies, studies on cultural transfer, and entangled histories all reveal different aspects of examined societies and individuals. They all belong to historians’ working tools.